PENGEMBANGAN E-MODUL PEMBELAJARAN PjBL - STEM LEARNING DENGAN STRATEGI JIGSAW PADA MATERI GERAK DAN GAYA UNTUK MENINGKATKAN KREATIVITAS DAN KETERAMPILAN BERKOMUNIKASI SISWA KELAS VII. - Ayu Ariyani; Anna Permanasari; Irvan Permana (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to create a PjBL-STEM-based learning e-module that can improve student creativity and communication skills on motion and force materials. This research method uses Research and Development (R&D), ADDIE design which consists of 5 stages (Analiysis, Design, Development, Implementation, Evaluation). Class VII students were involved as research subjects taken with purposive sampling technique. Research data were collected through creativity test, performance test, student response questionnaire and observation sheet. Data processing techniques for the improvement of creative thinking and communication skills used paired sample t-test and then N-Gain test. The results of the analysis showed that after using the PjBL-STEM-based learning e-module there was a significant increase in creative thinking with an N-Gain value of 60% in the medium category and an N- Gain value of 61% for improving communication skills. Student testing of creative products based on display criteria, functional prototypes and technological accommodations fall into the good category. In addition, students gave a positive response to the learning e-module of 47.79% for very good criteria and 45.6% for good criteria. Thus, the PjBL-STEM-based learning e-module with Jigsaw strategy can be used in science learning in grade VII to improve students' creativity and communication skills.